Peningkatan Hasil Belajar Peserta Didik Materi Sudut Menggunakan Model Cooperative Learning Tipe Make a Match di Kelas V Sekolah Dasar - Utami, Anissa Dwi; Helsa, Yullys (Asian Journal of Early Childhood and Elementary Education, 2025)
This study was motivated by the low mathematics learning outcomes of students. The aim of this research is to describe the improvement in learning outcomes through the Cooperative Learning model of the Make A Match type in the topic of Angles in Grade V of SDN 03 Geragahan, Agam Regency. This research is a Classroom Action Research (CAR) using both quantitative and qualitative approaches, conducted in two cycles. The research subjects consisted of 19 students, the class teacher as an observer, and the researcher as a practitioner. The results showed improvements in several aspects: the average score of the teaching module increased from 85.4% in the first cycle to 95.83% in the second cycle; teacher activity increased from 83.25% to 95.83%; student activity improved from 81.25% to 95.83%; and students’ average learning outcomes rose from 73.64% to 81,31%. Therefore, the implementation of the Cooperative Learning model of the Make A Match type has been proven to improve students’ mathematics learning outcomes in Grade V of SDN 03 Geragahan.